Gut Microbiota Dysbiosis Induced by Decreasing Endogenous Melatonin Mediates the Pathogenesis of Alzheimer’s Disease and Obesity - Zhang, Boqi; Chen, Tong; Cao, Maosheng; Yuan, Chenfeng; Reiter, Russel J.; Zhao, Zijiao; Zhao, Yun; Chen, Lu; Fan, Wenjing; Wang, Xin; Zhou, Xu; Li, Chunjin (Frontiers in Immunology, 2022)
Lifestyle choices, external environment, aging, and other factors influence the synthesis of melatonin. Although the physiological functions of melatonin have been widely studied in relation to specific organs, the systemic effects of endogenous melatonin reduction has not been reported. This study evaluates the systemic changes and possible pathogenic risks in an endogenous melatonin reduction (EMR) mouse model deficient in the rate limiting enzyme in melatonin production, arylalkylamine N-acetyltransferase (Aanat) gene. Using this model, we identified a new relationship between melatonin, Alzheimer’s disease (AD), and gut microbiota. Systematic changes were evaluated using multi-omics analysis. Fecal microbial transplant (FMT) was performed to examine the role of gut microbiota in the pathogenic risks of EMR. EMR mice exhibited a pan-metabolic disorder, with significant transcriptome changes in 11 organs, serum metabolome alterations as well as microbiota dysbiosis. Microbiota dysbiosis was accompanied by increased gut permeability along with gut and systemic inflammation. Correlation analysis revealed that systemic inflammation may be related to the increase of Ruminiclostridium_5 relative abundance. Eight-month-old EMR mice had AD-like phenotypes, including Iba-1 activation, A  protein deposition and decreased spatial memory ability. Moreover, EMR mice showed decreased anti stress ability, while under high-fat diet they had greater body weight and more obvious hepatic steatosis compared with WT group. FMT improved gut permeability, systemic inflammation, and AD-related phenotypes, while reducing obesity in EMR mice. Our findings suggest EMR causes systemic changes mediated by gut microbiota dysbiosis, which may be a pathogenic factor for AD and obesity, we further proved the gut microbiota is a potential target for the prevention and treatment of AD and obesity.